2012 IEEE Aerospace Conference 2012
DOI: 10.1109/aero.2012.6187178
|View full text |Cite
|
Sign up to set email alerts
|

Tunable narrow linewidth laser source for a methane lidar

Abstract: A high efficiency, narrow linewidth tunable laser source is developed for greenhouse trace gas remote sensing. It features broad, continuous tuning range at 1570 -1655 nm and 3291 nm with narrow linewidth (500 MHz) and high spectral purity. This laser is based on seeded optical parametric generator (OPG) technology. Several trace gas species were continuously detected for 72 hours in an open path environment. We also present our recent airborne experiment result based on this laser technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In this configuration, we have observed that the OPA output linewidth does not fully converge to the seed linewidth, giving wide side lobes, especially when pump and seed fluences are high and low, respectively. 52 Similar side lobes were observed in the seeded QPM-based OPA system for a CO 2 lidar. 53 Back conversion and parametric amplification of the seed's side lobes are possible causes.…”
Section: Discussionsupporting
confidence: 58%
“…In this configuration, we have observed that the OPA output linewidth does not fully converge to the seed linewidth, giving wide side lobes, especially when pump and seed fluences are high and low, respectively. 52 Similar side lobes were observed in the seeded QPM-based OPA system for a CO 2 lidar. 53 Back conversion and parametric amplification of the seed's side lobes are possible causes.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, for a space mission we are aiming for a simple and efficient single stage -not a complex multi-stage -OPA based on quasi-phase matching (QPM). In this configuration, we have observed that the OPA output linewidth does not fully converge to the seed linewidth, giving wide side lobes, especially when pump and seed fluences are high and low, respectively 49 . Back-conversion and parametric amplification of the seed's side lobes are possible causes.…”
Section: Gsfc Measurement Approachmentioning
confidence: 97%
“…The development of the OPA technology for LIDAR use has been discussed in detail previously. 18,20 We scan the LIDAR wavelength by changing the injection current of the DFB LD. 18,19 Our pulsed LIDAR uses 20 wavelengths spanning 17.6 GHz (0.16 nm) around the 1650.9 nm methane transition.…”
Section: Measurement Approach and Instrumentmentioning
confidence: 99%